2004
DOI: 10.1080/02699930341000022
|View full text |Cite
|
Sign up to set email alerts
|

Robust affective priming effects in a conditional pronunciation task: Evidence for the semantic representation of evaluative information

Abstract: Based on the hypothesis that information about the valence of words is encoded in a semantic system, we predicted that the match between the valence of a prime and the valence of a target word will influence the pronunciation of the target only if and to the extent that pronunciation is semantically mediated. In line with this prediction, we found affective priming effects (faster pronunciation when prime and target had the same valence than when they had a different valence) only when participants were instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
7

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 26 publications
4
56
0
7
Order By: Relevance
“…The finding of significant priming effects with the pronunciation task thus establishes a specific influence of facilitated target access processes on priming effects. Robust priming effects with the pronunciation task have repeatedly been demonstrated for associative prime-target pairs (e.g., Meyer et al, 1975; see Neely, 1991, for a review), whereas for categorically related prime-target pairs (e.g., affective priming), highly inconsistent results have been reported, including congruency, incongruency, Cognitive Processes in Categorical and Associative Priming 8 as well as null effects (e.g., Bargh et al, 1996;De Houwer & Randell, 2004;Glaser & Banaji, 1999;Hermans, De Houwer, & Eelen, 1994; Klauer & Musch, 2001; Schmitz & Wentura, in press;Spruyt, De Houwer, & Hermans, 2009; Spruyt, Hermans, De Houwer, & Eelen, 2002;Spruyt, Hermans, Pandelaere, De Houwer, & Eelen, 2004;Spruyt, Hermans, De Houwer, Vandromme, & Eelen, 2007;Wentura & Frings, 2008; see Klauer & Musch, 2003, andRothermund, 2003, for reviews).Similarly, using a categorization task that is unrelated to the dimension for which category congruency effects are investigated (e.g., an animacy categorization task is used when testing for affective category priming) should eliminate response competition as a potential explanation of categorical priming effects (but see Schmitz & Wentura, in press).Moreover, since post-lexical mechanisms are most plausible for the lexical decision task (see above) this strategy should also eliminate post-lexical mechanisms. Categorical priming effects are typically eliminated in designs in which the task is to categorize the targets according to another dimension (e.g., De Houwer et al, 2002;Klinger et al, 2000; Klauer & Musch, 2002; but see Spruyt, De Houwer, Hermans, & Eelen, 2007; Schmitz & Wentura, in press).…”
mentioning
confidence: 98%
“…The finding of significant priming effects with the pronunciation task thus establishes a specific influence of facilitated target access processes on priming effects. Robust priming effects with the pronunciation task have repeatedly been demonstrated for associative prime-target pairs (e.g., Meyer et al, 1975; see Neely, 1991, for a review), whereas for categorically related prime-target pairs (e.g., affective priming), highly inconsistent results have been reported, including congruency, incongruency, Cognitive Processes in Categorical and Associative Priming 8 as well as null effects (e.g., Bargh et al, 1996;De Houwer & Randell, 2004;Glaser & Banaji, 1999;Hermans, De Houwer, & Eelen, 1994; Klauer & Musch, 2001; Schmitz & Wentura, in press;Spruyt, De Houwer, & Hermans, 2009; Spruyt, Hermans, De Houwer, & Eelen, 2002;Spruyt, Hermans, Pandelaere, De Houwer, & Eelen, 2004;Spruyt, Hermans, De Houwer, Vandromme, & Eelen, 2007;Wentura & Frings, 2008; see Klauer & Musch, 2003, andRothermund, 2003, for reviews).Similarly, using a categorization task that is unrelated to the dimension for which category congruency effects are investigated (e.g., an animacy categorization task is used when testing for affective category priming) should eliminate response competition as a potential explanation of categorical priming effects (but see Schmitz & Wentura, in press).Moreover, since post-lexical mechanisms are most plausible for the lexical decision task (see above) this strategy should also eliminate post-lexical mechanisms. Categorical priming effects are typically eliminated in designs in which the task is to categorize the targets according to another dimension (e.g., De Houwer et al, 2002;Klinger et al, 2000; Klauer & Musch, 2002; but see Spruyt, De Houwer, Hermans, & Eelen, 2007; Schmitz & Wentura, in press).…”
mentioning
confidence: 98%
“…Spreading activation in semantic memory (Collins & Loftus, 1975;DeCoster & Claypool, 2004;De Houwer & Randell, 2004;Ross & Bower, 1981) strictly predicts congruity. It is hardly possible to invent an associative network architecture that predicts incongruity.…”
Section: Theoretical Implications Of the Predicted Strategic Ep Effectsmentioning
confidence: 99%
“…However, they are more easily remembered and recognized in both immediate (e.g., Hadley & MacKay, 2006;Monnier & Syssau, 2008) and delayed (e.g., Doerksen & Shimamura, 2001;Ferré, 2003) memory tests. Moreover, distinct psycholinguistic tasks, such as lexical decision (e.g., Carretié et al, 2008;Hofmann, Kuchinke, Tamm, Võ, & Jacobs, 2009;Wentura, 2000), pronunciation (e.g., de Houwer & Randell, 2004;Spruyt, Hermans, de Houwer, Vandromme, & Eelen, 2007), and evaluative categorization (e.g., de Houwer, Hermans, Rothermund, & Wentura, 2002;Gibbons, 2009;Hermans, de Houwer, & Eelen, 2001;Spruyt et al, 2007;Wentura & Degner, 2010), have shown that positive and negative words elicit lower reaction times and higher accuracy rates than do neutral words. Emotional words have also been shown to induce affective priming in both masked (e.g., Gibbons, 2009;Wentura & Degner, 2010) and unmasked (e.g., Hermans et al, 2001;Spruyt et al, 2007) designs.…”
Section: Introductionmentioning
confidence: 99%